2008
DOI: 10.1007/s00284-007-9065-9
|View full text |Cite
|
Sign up to set email alerts
|

Cys31, Cys47, and Cys195 in BinA Are Essential for Toxicity of a Binary Toxin from Bacillus sphaericus

Abstract: The mosquito larvicidal binary toxin produced by Bacillus sphaericus is composed of 2 proteins called BinA and BinB. While BinB acts as specificity determinant, BinA is expected to bind to BinB, translocates into cytosol, and exerts its activity via an unknown mechanism. To study the role of cysteine in BinA, 3 cysteine residues were substituted by alanine and serine. Substitution at Cys195 significantly reduced the toxin activity, whereas substitution at Cys31 and Cys47 abolished its toxicity. Intrinsic fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…A faint band of BinB dimer observed in non-reducing condition was likely the result of random intermolecular disulfide bond formation. Previous studies on cysteine mutagenesis in BinA also showed similar results in which the cysteine residues are not involved in disulfide bond formation within the BinA molecules (17). It is proposed that in solution binary toxin exists as tetramer composing of 2 molecules of BinA and 2 molecules of BinB, but the oligomer is not held together by disulfide bonds (13).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…A faint band of BinB dimer observed in non-reducing condition was likely the result of random intermolecular disulfide bond formation. Previous studies on cysteine mutagenesis in BinA also showed similar results in which the cysteine residues are not involved in disulfide bond formation within the BinA molecules (17). It is proposed that in solution binary toxin exists as tetramer composing of 2 molecules of BinA and 2 molecules of BinB, but the oligomer is not held together by disulfide bonds (13).…”
Section: Resultssupporting
confidence: 61%
“…However, amino acids in BinB participating in these interactions have not been identified. It was reported that cysteine residues in BinA are required for full toxicity of binary toxin, although it is unclear which step these cysteines may be involved in (17). BinB also contains 3 cysteine residues in the active core at positions 67, 161, and 241.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several amino acids have been identified with importance in maintaining the activity of the Bin proteins (Boonyos et al, 2009;Elangovan et al, 2000;Promdonkoy et al, 2008;Sanitt et al, 2008;Shanmugavelu et al, 1998;Yuan et al, 2001) and determining its level of activity against A. aegypti . Residue 150 was suggested to be important in receptor binding by BinB (Singkhamanan et al, 2010) and further, recent work has identified the region from residues 33-158 to be important for receptor binding, with residues 147-149 being critical to binding (Romao et al, 2011).…”
Section: Bin Structurementioning
confidence: 97%
“…Cys187 is conserved in all the toxins within this family, except Cry36. It is interesting to note that replacement of the Cys187-equivalent residue in BinA (Cys195) drastically reduces its activity [31] while substitution of the equivalent in BinB (Cys241) has no effect [32].…”
Section: Resultsmentioning
confidence: 99%